Hydrogen Sulfide: A Gaseous Molecule in Postharvest Freshness - Jianqiang Huo; Dengjing Huang; Jing Zhang; Hua Fang; Bo Wang; Chunlei Wang; Weibiao Liao (Frontiers in Plant Science, 2018)
Hydrogen sulfide (H2S), as a signaling molecule, is involved in the regulation of growth and development in plants. Recent studies have indicated that H2S also plays important roles in regulating postharvest senescence of horticultural products. The focus of this review is to summarize the synthesis of H2S in plants and its potential roles in alleviating the senescence of cut flowers, fruits, and vegetables during postharvest storage. During postharvest of horticultural products, H2S could scavenge reactive oxygen species via promoting the activity of antioxidant enzymes, thereby, sustaining the integrity of the membrane. In fruits, H2S effectively enhanced the tolerance of chilling by increasing the content of proline and polyphenol compounds. During postharvest storage of perishable fruits and vegetables, H2S significantly alleviated decay, which was caused by fungi by inhibiting the growth of fungi spores. Moreover, H2S interacted with other molecules synergistically (NO) or antagonistically (ethylene) to alleviate senescence of horticultural products. At the transcriptional level, H2S regulated the expression of senescence-related genes, which were related to degradation of proteins and chlorophyll, to delay the senescence of horticultural products. Thus, H2S does not only possess positive antioxidant and antifungal properties, but also significantly regulates the senescence-related gene during postharvest of horticultural products. Future studies of H2S in postharvest storage should focus on its molecular mechanism in the posttranslational modifications of proteins as well as its safety attributes in treated fruits and vegetables.